Sleep Assessment in Long COVID Clinics: A Necessary Tool for Effective Management. Issue 1 (18th February 2023) - Khosla, Seema; Cheung, Joseph; Gurubhagavatula, Indira; ,
Abstract : As we adapt to SARS-CoV-2, it has become apparent that the acute illness is not the only threat from this virus. Long COVID has emerged as a potentially disabling condition with multiple varied symptoms. We propose that querying patients about their sleep may allow for the assessment of a sleep-related disorder that is amenable to treatment. In addition, hypersomnolence is a prominent feature and may mimic other organic hypersomnias; therefore, inquiring about COVID-19 infection in sleepy patients is suggested.